The prognostic role of circulating tumor cells in heavily pretreated individuals with a low life expectancy. (December 2014) - Stebbing, Justin; Harding, Victoria; Urch, Catherine E; Kaier, Thomas; Schofield, Guy; Flook, Matthew; Alifrangis, Constantine; Young, Anna-Mary; Shaw, Jacqueline A; Coombes, R Charles; Krell, Jonathan
ABSTRACT : Aims: Studies of circulating tumor cells (CTCs) have generally recruited individuals with newly diagnosed metastatic cancer, with recent data also indicating their prognostic value in the adjuvant setting. Their role in dying patients has not been established.Experimental: CTCs were measured in 43 individuals with metastatic breast cancer estimated to have less than 6 months to live who had exhausted standard therapeutic options.Results: Those with a CTC count of ≤100 had a median of 182 days to live, compared with those with a CTC count of >100 who had a median of 17 days until death (p = 0.009, log rank, HR: 3.1, 95% CI: 1.4–7.3).Conclusion: A CTC count of >100 is associated with imminent death. Provided external validity is demonstrated, such information would be useful for patients and their families who often request specific prognostic clarity and could improve the quality of end-of-life care.